Protocol for CRISPR-based endogenous protein tagging in mammalian cells - Yu-Xi Xiao; Jiarun Wei; Jason Moffat (STAR Protocols, 2024)
Summary: Tracking the localization and proximal interaction partners of endogenous proteins provides valuable functional insight. Here, we present a protocol for CRISPR-based endogenous protein tagging in mammalian cells. We describe steps for endogenously tagging human TSC22D2 and MAP4, including designing Cas9 and Cas12a guides for knockin, modularized repair template design and cloning, and procedures for lipid transfection and electroporation. This protocol accommodates Cas nucleases in plasmid expression or ribonucleoprotein complex (RNP) formats. This “endo-tagging” approach offers flexibility and broad applicability.For complete details on the use and execution of this protocol, please refer to Xiao et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.